Perilaku Dinamik Motor Induksi Pada Dual Frequency Supply - Hariz Santoso, Asfari; Imron Ridzki; Lukman Hakim; Popong Effendrik; Priya Surya Harijanto; Adam Amrullah Wijaya (Elposys: Jurnal Sistem Kelistrikan, 2025)
The application of induction motors is currently very broad, one of which is in the fertilizer industry as a motor for vibrating screens with an auto clean mechanism. In this application, the induction motor is operated with two frequency values of 50 Hz during screening and 60 Hz during the auto clean process. The difference in frequency affects the dynamic characteristics of the induction motor. Especially when operated above the rated frequency, it will result in an increase in motor temperature so that regular monitoring of the motor temperature is needed. This study produces the dynamic characteristics of the motor when the supply frequency is 50 Hz with a transient condition duration of 0.5 seconds and a torque at steady state conditions of 25.89 Nm, while when the supply frequency is 60 Hz the transient condition duration is 0.5 seconds with a torque at steady state conditions of 31.03 Nm.